L’église Saint Joseph à Houmet Souk Djerba : Un lieu de culte et de marquage identitaire Maltais - Ben Amara, Manel (Al-Sabîl, 2021)
Keywords: Christianisme -- Djerba; Emigration -- Malte -- Djerba

Maltese migration in Tunisian Coastal Towns (1836-1844) : Sousse, Monastir, Mahdia, Sfax, Djerba and Moknine - Cassola, Arnold (Morrone, 2020)
Maltese migration in the 19th century was a result of the poor economic conditions on the island. Algeria and Tunisia proved to be amongst the most popular destinations for Maltese migrants in search of a better quality of life. The similarity between the Maltese and the Arabic language was considered to be an added bonus for the prospective Maltese migrant. In the case of Tunisia, as from around I 830 onwards thousands of Maltese migrated to this North African Regency, in particular to Tunis and its surroundings and to the various coastal towns. The first settlers were involved mainly in agricultural and fishing activities. In 1836 the Bey of Tunis gave permission to the Catholic Church to setup parishes in the country, which meant that baptisms, marriages and deaths of Catholics in Tunisia were registered and records were being preserved. In the course of the 19th century, the Maltese in Tunisia increased and expanded into a very large community. This work aims at reconstructing the number and names of the Maltese immigrants in the coastal towns of Sousse, Monastir, Mahdia, Sfax, Djerba and Moknine for the period between 1836 and 1844, through an investigation of the earliest baptism, marriage and death registers in the possession of the St. Felix Catholic Parish in Sousse. My research work and the publication of this book have been made possible through research funds made available by the University of Malta. Prof. Abdelaziz Messaoudi, of the University of Sousse, was instrumental in helping me out with logistic and academic issues related to the town of Sousse whilst Pere Fadiq and Pere Claudio, of the St. Felix Catholic Parish in Sousse, were always very patient with me whenever I went there to consult the parish archives. Finally, I must thank Victoria Attard Kingswell for her painstaking proofreading work and her valuable advice.
Keywords: Emigration -- Malte -- Djerba

Histoire de la colonie maltaise de Djerba - Maugan, Michèle (Patrimoine et Créativité, 2018)
Keywords: Emigration -- Malte -- Djerba

Malta and Tunisia, shared stories and common heritage - Taboubi, Abdellatif (Times of Malta, 2021)
If we go back in time, the ancient authors say that a king of Malta called Battus was on good terms with Queen Elyssa of Carthage. When she died by throwing herself into a blaze, her sister,  Anna found refuge in Malta, sheltered by this king. St Joseph church in Houmt el-Souk, in Djerba. In...
Keywords: Christianisme -- Djerba; Emigration -- Malte -- Djerba; Relations -- Djerba -- Malte

الجالية المالطية بجربة من خلال أوائل القرن 19 إلى أواسط القرن العشرين - بربو, المنصف (Les migrations des Jerbiens et autres insulaires méditerranéens à travers les siècles, 2013)
Keywords: Emigration -- Malte -- Djerba

‏الجالية الملطية في جزيرة جربة من أوائل القرن 19 إلى أواسط القرن 20 (1815-1964) - بربو, المنصف (جربة ومحيطها البحري والقاري: ‏بحوث في التاريخ والجغرافيا والحضارة‏: ‏أعمال الدورة 12 والدورة 13 لملتقى البشير التليلي, 2016)
Keywords: Emigration -- Malte -- Djerba

L’héritage impensé des Maltais de Tunisie - Muscat, Michèle (L'Harmattan, 2011)
Keywords: Emigration -- Malte -- Djerba

Les Maltais à Djerba : l’évolution d’une communauté étrangère - Mallia, David (Djerba, architecture, paysage et société, 2004)
École Nationale d’Architecture et d’Urbanisme de Tunis
Keywords: Emigration -- Malte -- Djerba

Histoire d'un Maltais de Tunis racontée à sa fille: récit intime - Sammut, Carmel (L'Harmattan, 2015)
Keywords: Emigration -- Malte -- Djerba

Rue des Maltais: la vie de la colonie maltaise de Tunisie - Donato, Marc (Collection Histoire des temps coloniaux, 2002)
Keywords: Emigration -- Malte -- Djerba

Murder in Jerba: Honour, Shame and Hospitality among Maltese in Ottoman Tunisia - Smith, Andrea (History and Anthropology, 2004)
Keywords: Emigration -- Malte -- Djerba